Pengaruh Fitur Layanan, Kepercayaan dan Keamanan Terhadap Minat Menggunakan Gopay di Kota Samarinda - Yunanto, Ricco; Asnawati, Asnawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the influence of service features, trust, and security on the intention to use GoPay in Samarinda City. The use of GoPay plays an important role in the digitalization of the Samarinda community however, there are several challenges, such as low interest in using digital products and the continued reliance on conventional methods. Therefore, a modern payment tool is needed. This study uses a quantitative approach with data collection techniques through questionnaires. The results of this study indicate that service features, trust, and security have a positive and significant effect on the intention to use GoPay in Samarinda City.